2021
DOI: 10.3390/cancers13163934
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Metabolism of Flavonoids by Gut Microbiota and Its Impact on Gastrointestinal Cancer

Abstract: Gastrointestinal (GI) cancer is a prevalent global health disease with a massive burden on health care providers. Internal and external factors such as obesity, smoking, diet (red meat), low socioeconomic status and infection with Helicobacter pylori are the critical risk factors of GI cancers. Flavonoids are natural phenolic compounds found abundantly in fruits and vegetables. Upon ingestion, 90% of flavonoids consumed require further enzymatic metabolism by the gut microbiome to enhance their bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 176 publications
1
18
0
Order By: Relevance
“…This review on flavonoids’ antimicrobial and anticancer action is in line with recent literature ( Al-Ishaq et al, 2021 ; González et al, 2021 ; Li et al, 2022 ). Altogether, data demonstrate the great potential of these compounds in combating H. pylori infection and gastric cancer protection.…”
Section: Future Directionssupporting
confidence: 79%
“…This review on flavonoids’ antimicrobial and anticancer action is in line with recent literature ( Al-Ishaq et al, 2021 ; González et al, 2021 ; Li et al, 2022 ). Altogether, data demonstrate the great potential of these compounds in combating H. pylori infection and gastric cancer protection.…”
Section: Future Directionssupporting
confidence: 79%
“…Carotenoids are one of the lipids that are bioactive and well recognized for their antioxidant activities and regulation of cellular growth and immune response ( Al-Ishaq et al., 2020 ). Flavonoids, natural phenolic compounds found abundantly in fruits and vegetables, were reported to have potentially anti-neurodegenerative, anti-inflammatory, anti-cardiovascular activities and anticancer abilities ( Al-Ishaq et al., 2021 ). In addition, several studies have shown that Fusobacterium_nucleatum is an emerging pathogen, which has been implicated as a causal microbe in several diseases of the gastrointestinal tract, including CD and colorectal cancer ( Cochrane et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on their chemical structure, flavonoids are segregated into various classes, among which there are further subclasses [29,30]. They were extensively studied and recently gained increased interest among researchers and clinicians for their antimicrobial, antioxidant, anti-inflammatory, anti-cancer, and antiviral properties with numerous mechanisms to prevent infection and strengthen host immunity [31][32][33][34][35][36][37]. Among their many beneficial effects, antiviral properties can serve as a future therapeutic utility for drugging COVID-19.…”
Section: Introductionmentioning
confidence: 99%